Duodenal ulcer promoting gene: effects on the pathophysiology of Helicobacter pylori infection and the host immune response - Ingram, Richard J.M. (2017)
Duodenal ulceration remains a significant problem. Helicobacter pylori infection is the major cause of duodenal ulcers (DU). Worldwide, around 1 in 2 people are chronically colonised by H. pylori, most of whom will not develop gastroduodenal disease, though some will develop DU whilst others will develop gastric ulcer or gastric carcinoma. The risk of disease is related to bacterial virulence factors, host and environmental factors. Disease-specific bacterial risk factors have not been established.